Cannabinoids, Inner Ear, Hearing, and Tinnitus: A Neuroimmunological Perspective - Perin, Paola; Mabou Tagne, Alex; Enrico, Paolo; Marino, Franca; Cosentino, Marco; Pizzala, Roberto; Boselli, Cinzia (Frontiers in Neurology, 2020)
Cannabis has been used for centuries for recreational and therapeutic purpose. Whereas the recreative uses are based on the psychotropic effect of some of its compounds, its therapeutic effects range over a wide spectrum of actions, most of which target the brain [Kendall and Yudowski 2017; Radhakrishnan and Ross 2018] or the immune system [Cabral et al. 2015]. Several studies have found cannabinoid receptors in the auditory system, both at peripheral and central level, thus raising the interest in cannabinoid signaling in hearing, and especially in tinnitus, which is affected also by anxiety, memory and attention circuits [Chen et al. 2015, Rauschecker et al. 2010, Rauschecker et al. 2015] where cannabinoid effects are well described [Bhattacharyya et al.2015; Lutz 2017]. Available studies on animal models of tinnitus (reviewed in Zheng and Smith 2019), suggest that cannabinoids are not likely to be helpful in tinnitus treatment, and could even be harmful. However, the pharmacology of cannabinoids is very complex, and most studies focused on CB1Rs, which are the main neural cannabinoid receptors. Cannabinoid effects on the immune system (where CB2Rs predominate [Turcotte et al. 2016]) are increasingly recognized as essential in understanding nervous system pathological responses [Chiurchiù et al. 2015a], and data on immune cannabinoid targets have emerged in the auditory system as well. This review will focus on neuroimmunological mechanisms for cannabinoid effects and their possible use as protective and therapeutic agents in the ear and auditory system.